2020
DOI: 10.1038/s41598-020-74456-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive potential does not cause loss of heat shock response performance in honey bees

Abstract: In other species characterized to date, aging, as a function of reproductive potential, results in the breakdown of proteaostasis and a decreased capacity to mount responses by the heat shock response (HSR) and other proteostatic network pathways. Our understanding of the maintenance of stress pathways, such as the HSR, in honey bees, and in the reproductive queen in particular, is incomplete. Based on the findings in other species showing an inverse relationship between reproductive potential and HSR function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Reproduction associated heat shock responses are inconsistent in different species, which is downregulated after the onset of reproduction in C. elegans [4] while in honey bees, increased reproduction did not cause loss of heat shock response in the reproductive queen [3]. In B. tabaci, mating led to the upregulation of Hsp68 and Hsp70 genes at different time points in mated females [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduction associated heat shock responses are inconsistent in different species, which is downregulated after the onset of reproduction in C. elegans [4] while in honey bees, increased reproduction did not cause loss of heat shock response in the reproductive queen [3]. In B. tabaci, mating led to the upregulation of Hsp68 and Hsp70 genes at different time points in mated females [20].…”
Section: Discussionmentioning
confidence: 99%
“…In honey bees, however, increased reproduction did not cause loss of heat shock response in the reproductive queen [3]. Therefore, honey bee queens may possess an atypical uncoupling of the reproduction-maintenance trade-off, in which stress response may be maintained during reproduction [3]. Therefore, study on the trade-offs between reproduction and survival in different mating systems by using methods that can more comprehensively examine various indicators (such as high-throughput sequencing and bioinformatics) will provide deeper insights in this field.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…These studies on different insect species, based on depth sequencing and bioinformatics, have provided further insights in this field. In addition, some of these studies also showed that mating may trigger trade-offs between reproduction and soma maintenance (such as immunity, stress response, DNA/protein repair and longevity) [ 39 , 40 ]. For instance, a recent study in S. litura , based on female whole-body RNA sequencing (RNAseq) analysis, found that mating may induce a trade-off between immunity and reproduction [ 41 ].…”
Section: Introductionmentioning
confidence: 99%